Possession Disorder in Makassar Indonesia - Siswanto Siswanto; Subandi Subandi; Ira Paramastri; Asniar Khumas (Faculty of Psychology, Diponegoro University, 2021)
This study discusses the occurrence of possession disorders in Makassar. The method used is a qualitative grounded theory method with data collection using semi-structured interviews and focus group discussions. The participants were three women, each of whom had experienced at least two possession disorders. The criteria for possession disorder refer to PPDGJ III. The results indicated that parenting, the role of the father figure, and the relationship with the mother, as well as the transmission of abusive religious beliefs were more likely the causes of possession disorders in the Makassar/Indonesian context. The abuse experienced is more related to parenting patterns than physical or sexual abuse as appears in the Western literature. Future research that deepens parenting themes and religious beliefs is important to understand the occurrence of other psychopathologies besides possession disorders.